Characteristics of Rapid Visco Analyzer Carrageenan Extract with Enzymatic Pretreatment of Kappaphycus striatum - Hendrawan Laksono; Citra Kusumaning Dyah; Renny Primasari Gustia Putri; Maya Soraya; Heri Purwoto (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Carrageenan is a polysaccharide compound extracted from red seaweed and is widely used by food, cosmetic, and advanced materials industries because of its good properties as an environmentally friendly stabilizer. Carrageenan extraction generally uses alkaline treatment for one full day, where the treatment is to obtain carrageenan quality with good gel characteristics. The use of cellulase enzymes is thought to accelerate the desulfuration process of seaweed, where cellulase enzymes are used to break down cellulose in seaweed cell walls. By using a rapid visco analyzer (RVA), carrageenan was tested to see the pattern and viscosity value. This study aims to determine the effect of enzymatic pretreatment on the profile of carrageenan with a shorter alkalization process compared to the alkalization commonly used by the industry. The results showed that enzymatic treatment before KOH alkalization would produce a carrageenan profile with a viscosity value of 272-360 cP, whereas the NaOH alkalization only reached 19-24 cP. The results of the test using RVA showed that the addition of an enzymatic process could change the physicochemical properties, such as viscosity and gel point of the carrageenan alkalinized with KOH. However, there was no significant difference in the properties when treated by alkalization using NaOH, which can be described from the value of the gelling point of carrageenan treated by cellulose enzyme. Adding enzymes to KOH will accelerate the gelation process, which occurs at an average temperature of 42.78oC. Meanwhile, carrageenan without enzymatic addition has an average gelation value of 37.48oC.